Universal features of the nuclear matrix elements governing the mass sector of the 0νββ decay - Civitarese, Enrique Osvaldo (2005)
In this work we report on manifest universal features found in the nuclear matrix elements which govern the mass sector of the neutrinoless double beta decay. The results are based on the analysis of the calculated matrix elements corresponding to the decays of 76Ge, 82Se, 100Mo, and 116Cd. The results suggest a dominance of few low-lying nuclear states of few multipoles in these matrix elements. Dedicated charge-exchange reactions could be used to probe these key states to determine experimentally the value of the nuclear matrix element.